Caracterización de estados emocionales en estudiantes universitarios en riesgo de presentar Trastornos de Adaptación. - Acosta García, Yanet (Universidad Central “Marta Abreu” de Las Villas, 2012)
La presente investigación se realizó con el objetivo de comparar manifestaciones de los estados emocionales: ansiedad, depresión, ira y estrés académico en estudiantes de ambos sexos, entre 18 y 21 años de edad en riesgo de presentar Trastorno de Adaptación y sus pares escolares sin este antecedente que cursan primero y segundo año en la Facultad de Matemática Física y Computación de la Universidad Central “Marta Abreu” de Las Villas, en el período comprendido del mes de enero a abril de 2012. Se realizó un estudio transversal, exploratorio, no experimental descriptivo. Se conformaron dos grupos de 25 miembros, integrados por estudiantes, en riesgo de padecer Trastorno de Adaptación y sus pares escolares que no poseen este riesgo. Fueron aplicadas un conjunto de técnicas, entre las que se encuentran: entrevista psicológica semi-estructurada, Cuestionario Exploratorio Inicial, Fuentes de Estrés Académico, Cuestionario de aislamiento y soledad, Inventario de Ansiedad Rasgo-Estado (IDARE),Inventario de Depresión Rasgo-Estado (IDERE),Inventario de autoestima, de expresión de la ira estado-rasgo (STAXI - 2) y Escala de Sucesos de Vida. Para el procesamiento de los datos se utilizaron los programas U de Mann Whitney y W de Wilcoxon, incluídos en el SPSS. Entre los principales resultados se destacan elevados niveles de estrés académico e índices de aislamiento y soledad en ambos grupos de estudio. Se apreciaron altos niveles de ansiedad y depresión rasgo-estado en el grupo de estudio, así como bajos niveles de autoestima que los diferencian de sus pares. Sobresalen factores de riesgo como estrés académico y problemas familiares. Se encontraron factores protectores tales como aceptación grupal y estar estudiando una carrera universitaria. Se ofrecen conclusiones y recomendaciones que pueden ser de interés para fortalecer las acciones de atención psicoeducativa y promover el desarrollo de futuras investigaciones.

This present investigation was carried out with the objective of comparing the manifestations of emotional states of anxiety, depression, anger and academic stress in students of both sexes among 18 and 21 years old. One group of these students took courses in first and second year of racing, Bachelors in Mathematics, Physics and Computer Sciences, and are at risk ofhaving an adjustment disorder and the other group of students are those who does not manifest the antecedents mentioned above and belonged tothe Faculty of the University Central Marta Abreu of the Villas, in the time of January to April 2012. A transverse non experimental descriptive study was achieved. Two groups of students were formed, each integrated by 25 members; those at risk of sufferingan Adjustment Disorder and their classmates that were not at risk.Information was obtained from the pedagogical authorities and teachers of the Faculty, and of students, the ones to whom a set of techniques were applied. Amongst the techniques applied were: Psychological semi-structured interview, Exploratory questionnaire, Questionnaire of Academic Stress sources, Questionnaire of isolation and solitude of M.M.Casullo( ACS), Inventory of Anxiety Rasgo Estado ( IDARE ), Inventory of Depression as a characteristic and as a feature ( IDERE ),Inventory of self-esteem, Inventory of expression of anger state feature ( STAXI - 2 ) and Sucesos's scale of Vida of M.m.Casullo. The processing of data was accomplished with the utilization of programs U of Mann Whitney and W of Wilcoxon included in the SPSS version 11,0.Amongst the principal results to stand out were the elevated levels of academic stress and indices of isolation and solitude in both study groups. High Levels of anxiety and depression was estimated as characteristics or features in the study group, as well as low levels of self-esteem that differentiated the study groupfrom their classmates.It was observed that manifestations of anger did not show differences in the two groups, predominating low and moderate statuses.The risk factors that stand out are high academic stress and family problems. As part of the main protective factors found are;the presence of people emotionally significant for them, group acceptance and studying at a university.This study offers conclusions and recommendations that can be of interest to strengthen psychological actions as well as educational attention to these students and promoting the development of future investigations.
Keywords: Estudiantes Universitarios; Estados Emocionales; Estrés Académico; Riesgo de Trastorno de Adaptación.; University Students; Emotional Statuses; Academic Stress; Trastorno's Risk of Adaptation